Hukum Perikatan dalam Kontrak Internasional dan Implikasinya - Umdah Aulia Rohmah; Rabith Madah Khulaili Harsya; Muhammad Arfianto Pandu W; Rifka Novia Ardhita Putri (Jurnal Syntax Admiration, 2025)
In an era of increasingly complex globalization, the legal regulation of international agreements is very important to ensure legal certainty in cross-border contracts. Challenges faced in the recognition and enforcement of ties, including differences in legal systems, jurisdictional conflicts, and juridical obstacles. The law of engagement serves as the basis of legal relations binding the parties to a contract, but its implementation is often hampered by differences in legal procedures and public order principles in different countries. Harmonization of law through international treaties, such as the United Nations Convention on Contracts for the International Sale of Goods (CISG) and the 1958 New York Convention, is proposed as a solution to overcome these differences. In addition, international arbitration is recognized as an effective dispute resolution mechanism, providing flexibility and certainty for the parties. This research uses a qualitative method with a descriptive-analytical approach to explore the dynamics of international binding law and its implications for the enforcement of rights and obligations in the context of international civil law. The results show that strengthening the international legal framework and collaboration between countries is necessary to create a stable and predictable business environment.